Actitud de las gestantes frente al Covid 19 - Jiménez Ordóñez, Marie Alexandra; Valarezo Segovia, Cinthia Betzy; Saraguro Salinas, Sara Margarita (My University, 2021)
The evaluation of the attitude of pregnant women towards Covid-19 allows us to identify those deficit areas where we must act with patient education, on the other hand it helps us to evaluate the knowledge and beliefs that pregnant women have about SARS-CoV2, it also allows us to know how is the affective process of pregnant women, and what are the actions they take in the face of the pandemic. The main objective is to know what the attitudes of pregnant women are towards Covid-19, the specific ones are: To know the level of information that pregnant women have about prevention measures during this Covid-19 pandemic, Describe what is the emotional state of pregnant women during the pandemic, and Identify the prevention behaviors carried out by pregnant women during this pandemic. A questionnaire was implemented in which there were items that were scored with the Likert scale (from 1 to 5) according to the degree of satisfaction, there were also closed questions, with an answer of YES and NO. For the data reliability analysis, the SPSS Version-25 program was used. The sample was made up of 100 pregnant women. The results showed in cognitive attitudes that 92% of pregnant women know the prevention measures of Covid-19, while in affective attitudes they showed that 90% are afraid that the newborn is infected inside the Hospital during delivery or postpartum. Finally, in the behavioral attitude, only 30% of pregnant women wash their hands for at least 20 seconds or more
La evaluación de la actitud de las gestantes frente al Covid-19 permite identificar aquellas áreas deficitarias donde debemos actuar con la educación al paciente, por otra parte nos sirve para evaluar los conocimientos y creencias que tienen las embarazadas del SARS-CoV2, también permite saber cómo está el proceso afectivo de las gestantes, y cuáles son las acciones que toman ante la pandemia. El objetivo principal es conocer cuáles son las actitudes de las gestantes frente al Covid-19. Se implementó un cuestionario en donde hubo ítems que se puntuaron con la escala de Likert (de 1 a 5) según el grado de satisfacción, también hubo preguntas cerradas, con respuesta de SI y NO. Para el análisis de fiabilidad de datos se utilizó el programa SPSS Versión-25. La muestra la constituyeron 100 mujeres gestantes. Los resultados mostraron en las actitudes cognitivas que el 92% de las gestantes conocen las medidas de prevención del Covid-19, mientras que en actitudes afectivas mostraron que el 90% si tienen temor de que el recién nacido se contagie dentro del Hospital durante el parto o pos-parto. Finalmente, en la actitud conductual solo el 30% de las gestantes se lavan las manos al menos 20 segundos o más.
Keywords: GESTANTES; COVID-19; ACTITUDES DE LAS GESTANTES; EMOCIONES; PREVENCIÓN DEL COVID-19